2022
DOI: 10.55980/ebasr.v1i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Innovation of Electronic-Based Multipurpose Credit Services to Improve Customer Satisfaction Through Loan Fee : A Study on Bank Jatim - Malang

Abstract: The competition of financial services business is getting higher and encourages banks to optimize their efforts to reach as many prospective customers as possible. One of the efforts made is to update innovative banking credit services through the development of an electronic-based multipurpose credit service system. This research aims to find out whether the quality of service, product quality, and loan fee, affect customer satisfaction. This research uses a quantitative approach, data collection using questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The model in this study was developed from a combination of several studies by Pramarta and Netra (2018), Arasanmi andKrishna (2019), andTews et al (2020). However, there are differences in the variable indicators used, which are adjusted to the object of research at Bank Jatim (Orbaningsih, Gitaria, & Budi, 2022). Referring to the description of research phenomena and problems described IJSSR Page 1912 above and the research gaps found regarding the relationship between talent management and perceived organizational support to retention, further studies are needed in research entitled "The Effect of Talent Management and Perceived Organizational Support on Employee Retention Mediated by Organizational Commitment" (Study on Bank Jatim Branch Employees).…”
Section: Introductionmentioning
confidence: 99%
“…The model in this study was developed from a combination of several studies by Pramarta and Netra (2018), Arasanmi andKrishna (2019), andTews et al (2020). However, there are differences in the variable indicators used, which are adjusted to the object of research at Bank Jatim (Orbaningsih, Gitaria, & Budi, 2022). Referring to the description of research phenomena and problems described IJSSR Page 1912 above and the research gaps found regarding the relationship between talent management and perceived organizational support to retention, further studies are needed in research entitled "The Effect of Talent Management and Perceived Organizational Support on Employee Retention Mediated by Organizational Commitment" (Study on Bank Jatim Branch Employees).…”
Section: Introductionmentioning
confidence: 99%
“…The financial sector especially banking sector is one of the vital sectors deemed as backbone of the country's economy (Bhaskaran et al, 2016;Dikko et al, 2021;Hani et al, 2021;Thai et al, 2021), especially during economic recovery due to the pandemic. The role of banking is vital due its ability to absorb a large number of workers, provide a variety of credit and investment products and provide other financial services to the public (Alam et al, 2021;Orbaningsih et al, 2022). Meanwhile on investment side, the banking sector also occupies the largest capitalization on the Indonesia Stock Exchange, see also (Foggitt et al, 2017;Gallego-Sosa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the quality of a good page provider can increase positive emotions in the form of Happiness which has implications for tourists' behavioural intentions (Pujiastuti et al, 2017;Ratnasari et al, 2020). Tourists strive to feel a positive experience in an island destination to create satisfaction and Happiness through new and unique things (Orbaningsih et al, 2022). The tourist experience on an island can shape the Happiness and satisfaction of tourists (Saleh, 2021).…”
Section: Introductionmentioning
confidence: 99%